The Creating of Product to Value-Added of the Picked bamboo shoot Community Enterprises in Ban Na Kraseng, Tha Li, Loei - Kumyan, Jirawadee (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2026)
The Objectives of the research article were 1) Study the appropriate management context of the Na Kraseng Bamboo Shoot Community Enterprise Group, Tha Li District, Loei Province. 2) Develop bamboo shoot products to increase the income of the Na Kraseng Bamboo Shoot Community Enterprise Group, Tha Li District, Loei Province. 3) Analyze the cost, return, and financial value of the products of the Na Kraseng Bamboo Shoot Community Enterprise Group, Tha Li District, Loei Province. The researcher selected participatory action research, defined the target group by selecting 12 people, and used a structured interview form approved by experts. Data were collected by organizing meetings, organizing exchange forums, in-depth interviews, and brainstorming through focus group discussions. The data were analyzed using non-theoretical event analysis and descriptive statistics, including numbers and percentages. The research results found that 1) the group’s management potential is still insufficient. There are several problems, including a lack of knowledge in modern management, a shortage of raw materials in some seasons, inconsistent product quality, a lack of accurate cost analysis, and limited distribution channels. From these problems, the research team proposed a development approach that covers many dimensions, including developing the group’s management potential, creating a network of bamboo shoot farmers to solve the problem of raw material shortages, transferring knowledge on processing and the use of production technology, and promoting knowledge on cost calculation. Packaging development, as well as expanding marketing channels. 2) The development found that it can significantly increase the product value from 30 baht per kilogram to 75 baht per kilogram, an increase of 150%. In addition, technology is introduced into the production process, such as the use of a bamboo shoot cutting machine, which helps increase production efficiency and reduce raw material loss, as well as the development of both Upskill and Reskill skills for group members. 3) Financial analysis shows the value of the investment, with a production cost of 24.17 baht per bottle, while the selling price is 30 baht per bottle, a payback period of approximately 1 year and 6 months, a positive net present value of 103,906.42 baht, and a return on investment of 64%. The results of this research reflect the potential for sustainable development of community businesses, indicating that integrating cooperation from all sectors, developing group members' skills, and applying innovation in production and marketing can effectively elevate local products and generate additional income for the community.